Struggle for phosphorus and the Devonian overturn - Kraft, Petr; Mergl, Michal (Trends in ecology & evolution, 2022)
Organisms with external phosphatic shells diversified and became abundant at the beginning of the Early Paleozoic but gradually declined and were rare by its end. The decreasing availability of phosphorus in oceans is thought to be responsible for this evolutionary trend. Responses of organisms to changes in the phosphorus cycle can be traced to the late Neoproterozoic, and likely had a significant role in the Cambrian explosion, the Great Ordovician Biodiversification Event (GOBE), and the Devonian nekton revolution. Effective use of phosphorus by vertebrates during the Devonian nekton revolution caused the phosphorus pool to shift from benthic external shells to the skeletons of pelagic vertebrates, and moved the marine faunas toward the dominance patterns and ecological structure of the Modern Evolutionary Fauna.
Keywords: Animals; Devonian; obratlovci; phosphorus cycle; biodiverzita; Biodiversity; zvířata; biologická evoluce; Biological Evolution; shells; Phosphorus; Fossils; GOBE; phosphate; Vertebrates; zkameněliny; fosfor